DEVELOPMENT AND STUDY OF ALKALI-ACTIVATED CEMENTS AND CONCRETE BASED ON THEM USING CHPASH (Proceedings of International Educators Conference, 2023)
The possibilities of developing a resource-saving technology for the production of concrete mixtures using cullet as a coarse aggregate for the manufacture of monolithic floors are considered. The ways of using cullet as a material for construction, the prospects for its use as a filler for concrete have been studied. It is shown that cullet, the density of which is lower than the density of traditional aggregates, can serve as an excellent raw material and act as a concrete aggregate, as well as help reduce the cost of extracting natural resources and reduce energy for their processing.